2018
DOI: 10.1021/acsomega.7b02097
|View full text |Cite
|
Sign up to set email alerts
|

Heteroassembly Ability of Dicationic Ionic Liquids and Neutral Active Pharmaceutical Ingredients

Abstract: Extensive investigation of interactions and aggregation properties of IL + API systems is necessary to apply ionic liquids (ILs) with different hydrophobic characteristics to drug delivery or in active pharmaceutical ingredient (API) formulations. Therefore, this study aims to investigate the heteroassembly between dicationic ILs ([BisOct(MIM) 2 ][2X], in which X is Br or BF 4 , and [BisOct(BnIM) 2 ][2Br]), both in the absence and the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…This fact may be associated with the more lipophilic nature of ILs with longer chains, or because smaller chains can be eliminated more easily by the excretory system [ 36 ]. The toxic effects of the [C 8 (MIM) 2 ][2X] DILs (in which X = Br, BF 4 , NO 3 , SCN, and Cl) on the survival of C. elegans was previously reported, with the worms’ survival rate above 90%, thus indicating no significant toxicity for these ILs at 0.01–10 mg·L −1 [ 37 ]. Therefore, considering these results and the ones presented herein, it can be seen that the toxicity of DILs against C. elegans was lower than that of monocationic IL, which may be associated with the additional cationic moiety.…”
Section: Resultsmentioning
confidence: 99%
“…This fact may be associated with the more lipophilic nature of ILs with longer chains, or because smaller chains can be eliminated more easily by the excretory system [ 36 ]. The toxic effects of the [C 8 (MIM) 2 ][2X] DILs (in which X = Br, BF 4 , NO 3 , SCN, and Cl) on the survival of C. elegans was previously reported, with the worms’ survival rate above 90%, thus indicating no significant toxicity for these ILs at 0.01–10 mg·L −1 [ 37 ]. Therefore, considering these results and the ones presented herein, it can be seen that the toxicity of DILs against C. elegans was lower than that of monocationic IL, which may be associated with the additional cationic moiety.…”
Section: Resultsmentioning
confidence: 99%
“…Frizzo et al used isothermal titration calorimetry and other experiments to study the ability of hybrid assembly between cationic ILs in the presence or absence of neutral APIs with different functional groups . The results showed that API-IL binding occurred at extremely low IL concentration.…”
Section: Api-il For Enhancing Drug Deliverymentioning
confidence: 99%
“…To obtain further information on the interactions between the emulsion components, 1 H NMR spectra were also acquired for pristine ILs and in the presence of increased concentrations of MCT [29,30]. Spectra in the presence of fluconazole were not obtained because of the low solubility of this drug in water [31].…”
Section: Intermolecular Interactions Between the Emulsion Componentsmentioning
confidence: 99%